Cytotoxicity, Antimicrobial, and In Silico Studies of Secondary Metabolites From Aspergillus sp. Isolated From Tecoma stans (L.) Juss. Ex Kunth Leaves - Elsayed, Heba E.; Kamel, Reem A.; Ibrahim, Reham R.; Abdel-Razek, Ahmed S.; Shaaban, Mohamed A.; Frese, Marcel; Sewald, Norbert; Ebrahim, Hassan Y.; Moharram, Fatma A. (Frontiers in Chemistry, 2021)
Seven secondary metabolites namely, arugosin C (1), ergosterol (2), iso-emericellin (3), sterigmatocystin (4), dihydrosterigmatocystin (5), versicolorin B (6), and diorcinol (7) was isolated from the rice culture of Aspergillus sp. retrieved from Tecoma stans (L.) Juss. ex Kunth leaves using various chromatographic and spectroscopic techniques. Moreover, the anticancer and antimicrobial activity of the total ethyl acetate extract and isolated metabolites were evaluated as well as molecular docking was conducted using Auto Dock Vina platform to explore the binding affinity of the isolated metabolites to the ATP kinase domain of Hsp90 and DNA gyrase as proposed molecular targets. Compound 3 displayed the best cytotoxic effect on MCF-7 cells with IC50=225.21 µM, while 5 showed the foremost cytotoxicity on HepG2 cells with IC50=161.81 µM. The latter demonstrated a 60% apoptotic mode of cell death with high docking score of -8.4 Kcal/mol at the Hsp90 ATP binding cleft. On the other, compounds 4 and 5 displayed antimicrobial activity especially on Pseudomonas aeruginosa with MIC = 125  μg/mL. The observed effect may be likely related to the excellent affinity of the tested compounds to the bacterial DNA-gyrase with binding score -10.2796 to -12.3974 Kcal/mol. In all, Aspergillus sp. isolated from T. stans is a potential source for cytotoxic and antibacterial hits which need further investigation to novel therapeutic leads.